2013
DOI: 10.4110/in.2013.13.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Humoral and Cell-Mediated Immunity Against Avian Influenza and Newcastle Disease Vaccines by Oral Administration ofSalmonella entericaSerovar Typhimurium Expressing Chicken Interleukin-18

Abstract: Interleukin-18 (IL-18) has been known to induce interferon-γ (IFN-γ) production and promote Th1 immunity. Although mammalian IL-18 has been characterized in great detail, the properties and application of chicken IL-18 remain largely uninvestigated as of yet. In this study, we evaluated the immunomodulatory properties of Salmonella enterica serovar Typhimurium expressing chicken interleukin-18 (chIL-18) on immune responses induced by avian influenza (AI) and Newcastle disease (ND) vaccines. After oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
7
0
2
Order By: Relevance
“…It has been reported that the combined administration of chicken IFN-α (ChIFN-α) and ChIL-18 using a Salmonella vaccine strain is an effective immunization strategy against avian influenza H9N2 virus in chicken [Rahman et al, 2012]. The report has indicated that administering ChIL-18 may be a novel approach for protecting chicken from currently circulating avian influenza and Newcastle Disease virus strains [Rahman et al, 2013]. Many studies have shown that recombinant ChIL-18 boosts the immune responses to avian virus vaccines [Degen et al, 2005;Chen et al, 2010;Rahman et al, 2013], and in vitro studies have recently shown that, similar to IL-1 [Degen et al, 2005], IL-18 overexpression inhibits hepatitis B virus replication in a hepatoma cell line [Chen et al, 2010].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that the combined administration of chicken IFN-α (ChIFN-α) and ChIL-18 using a Salmonella vaccine strain is an effective immunization strategy against avian influenza H9N2 virus in chicken [Rahman et al, 2012]. The report has indicated that administering ChIL-18 may be a novel approach for protecting chicken from currently circulating avian influenza and Newcastle Disease virus strains [Rahman et al, 2013]. Many studies have shown that recombinant ChIL-18 boosts the immune responses to avian virus vaccines [Degen et al, 2005;Chen et al, 2010;Rahman et al, 2013], and in vitro studies have recently shown that, similar to IL-1 [Degen et al, 2005], IL-18 overexpression inhibits hepatitis B virus replication in a hepatoma cell line [Chen et al, 2010].…”
mentioning
confidence: 95%
“…The report has indicated that administering ChIL-18 may be a novel approach for protecting chicken from currently circulating avian influenza and Newcastle Disease virus strains [Rahman et al, 2013]. Many studies have shown that recombinant ChIL-18 boosts the immune responses to avian virus vaccines [Degen et al, 2005;Chen et al, 2010;Rahman et al, 2013], and in vitro studies have recently shown that, similar to IL-1 [Degen et al, 2005], IL-18 overexpression inhibits hepatitis B virus replication in a hepatoma cell line [Chen et al, 2010]. IL-18 is also required for the activation of NK cells in response to infections with vaccinia virus and murine cytomegalovirus and plays a critical role in antiviral defense [Su et al, 2011].…”
mentioning
confidence: 99%
“…As chIL-18 secreted from χ8501/chIL-18 was shown to induce nitric oxide (NO) production by HD-11 cells measured by Griess assay indicating IFN-γ release, the secreted chIL-18 was biologically active. Additionally, in vivo biological activity of chIL-18 secreted by χ8501/chIL-18 in chicken host system has been studied at our lab [18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Sel Th-1 dan ekspresi IL-18 dapat dideteksi pada hari ketiga pasca-vaksinasi ND inaktif. Sel IL-18 mampu menginduksi ekspresi sitokin IL-4 dan IFN-γ yang berperan penting dalam respon kekebalan Th-1 (Rahman et al 2013). Respon CMI lebih cepat muncul pada unggas yang divaksinasi dengan vaksin virus ND hidup (Reynolds & Maraqa 2000).…”
Section: Cell Mediated Immunityunclassified